Penerapan Soft Sistem Methodelogy Pada Pengembangan Sistem Informasi Akademik (Studi Kasus di SMKN 6 Kota Bekasi) - Ani Yoraeni; Henny Leidiyana (Journal of Informatic and Information Security, 2021)
Academic information systems are important in teaching and learning activities, this is supported by adequate facilities and infrastructure. To support this, a system must be made that is able to assist in the teaching and learning process, namely by developing an academic information system. This development system uses the social system methodology method with the aim of helping the school's academic field achieve its goals and facilitate the teaching and learning process. This approach is designed using CATWOE analysis with components, namely customers, actors, the transformation process, world view, and the environment. The results of this study are able to answer the school's need for an effective and efficient system so that it can improve the performance of all school goals.